Forensic Pathology of Infancy and Childhood - Collins, Kim A.; Byard, Roger W. (Springer New York : Imprint: Springer, 2014)
The investigation of sudden or unexplained death of children represents a unique medical and forensic area of study. Children have unique anatomic and functional characteristics that must be recognized and understood by the medical investigator. Further complicating this process is the fact that the anatomic structure, composition and function of various organs and organ systems in the pediatric population change throughout the developmental stages of childhood. The disease processes, reactions to trauma and risk factors for accidental death and homicide change from infancy through adolescence. Forensic Pathology of Infancy and Childhood provides an authoritative, comprehensive reference text devoted to the medicolegal investigation of sudden unexpected death in children. With contributions from internationally renowned experts, individual chapters focus on specific unique causes and organ systems with detailed accounts of the changes in fatal diseases, risk factors of causes of sudden death, and responses to fatal trauma that occur as a child grows from neonatal stage through infancy, toddlerhood, childhood and adolescence. This text is an essential reference resource for forensic pathologists, medical examiner offices, pediatric pathologists, pediatric hospitals, anatomic pathologists and those in training as well as those in related legal professions.